Enhancing Laboratory Testing Efficiency in Saudi Arabia: A Systematic Review of Best Practices for Laboratory Technicians and Specialists under Vision 2030 - Ali Abdullah Aysh Al Muhanna; Kawthar Ahmed Mohammed Almuaybid; Yaser Abdulmohsen S Al Aghnam; Hind Abdullah Hamed Albeladi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Saudi Arabia's Vision 2030 aims to transform the healthcare system, with a focus on improving the quality and efficiency of laboratory services. This systematic review explores best practices for laboratory technicians and specialists to enhance testing efficiency in the context of Vision 2030. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science databases. Studies that discussed best practices for laboratory professionals, the implementation of Vision 2030 in healthcare, and the Saudi Arabian context were included. The findings suggest that implementing standardized operating procedures, investing in advanced technology, providing continuous training and education, and fostering interprofessional collaboration are key strategies to improve laboratory testing efficiency. The review highlights the critical role of laboratory technicians and specialists in achieving the goals of Vision 2030 in the healthcare sector. Recommendations for policy, practice, and future research are provided to support the optimization of laboratory services and the realization of Vision 2030 objectives.